The relationship of work-family conflict and quality of work life among female nurses in Medan: Hubungan work-family conflict dengan quality of work life pada perawat perempuan di kota Medan - Manurung, Yulinda Septiani; Sirait, Jesica Tania; Marpaung, Winida (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2020)
This study examines the relationship between work-family conflict and the quality of work life among nurses in the city of Medan. The author hypothesized that higher level of work-family conflict would be associated with lower quality of work life. Participants were 105 female nurses from the city of Medan. We obtained the data using a questionnaire that measures work-family conflict and quality of work life. We analyzed the data using SPSS 17. The results showed a negative relationship between work-family conflict and quality of work life. Female nurses with higher work-family conflicts tended to have lower quality of work-life than those with lower work-family conflicts. Studi ini meneliti hubungan antara work-family conflict dengan quality of work life. Dihipotesiskan bahwa peningkatan work-family conflict akan diikuti dengan penurunan quality of work life. Partisipan penelitian adalah 105 perawat berjenis kelamin perempuan di kota Medan. Data diperoleh melalui kuesioner yang mengukur work-family conflict dan quality of work life. Data dianalisis menggunakan SPSS 17. Hasil penelitian menunjukkan hubungan negatif antara work-family conflict dengan quality of work life. Perawat dengan work-family conflict yang tinggi cenderung memiliki quality of work life yang rendah.